EVALUATION OF MATHEMATICAL MODELS WHICH DESCRIBE THE PROCESS OF DRYING GOAT MEAT - Olga DRĂGHICI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Drying is a step in the processing of goat meat. This paper presented the influence of salt and pH on moisture ratio over time, when the goat meat dries at 103°C, at thermobalance. From the obtained data it was observed that the water-holding capacity of goat meat was influenced only by lowering the pH by one unit. In the case of goat meat containing 3% salt, moisture ratio varied over time as in the case of the control sample. The mathematical models which describe the process of drying goat meat was investigated under each experiment conditions. An exponential variation of moisture ratio over time was obtained and this was best described by the exponential model named "Wang & Singh".